2017
DOI: 10.1073/pnas.1617374114
|View full text |Cite
|
Sign up to set email alerts
|

High serum serotonin in sudden infant death syndrome

Abstract: Sudden infant death syndrome (SIDS), the leading cause of postneonatal infant mortality, likely comprises heterogeneous disorders with the common phenotype of sudden death without explanation upon postmortem investigation. Previously, we reported that ∼40% of SIDS deaths are associated with abnormalities in serotonin (5-hydroxytryptamine, 5-HT) in regions of the brainstem critical in homeostatic regulation. Here we tested the hypothesis that SIDS is associated with an alteration in serum 5-HT levels. Serum 5-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 46 publications
(42 reference statements)
2
29
0
1
Order By: Relevance
“…An elevated serum levels of 5-HT has been observed in victims of SIDS (18). The present study showed, for the first time, that PNE doubles the 5-HT concentration in BALF (from 1.3 to 2.5 ng/ml) in rat pups, similar to the findings of the 5-HT protein level in blood (;4 ng/ ml), which is doubled by cigarette smoking for 6 wk in rats (53).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…An elevated serum levels of 5-HT has been observed in victims of SIDS (18). The present study showed, for the first time, that PNE doubles the 5-HT concentration in BALF (from 1.3 to 2.5 ng/ml) in rat pups, similar to the findings of the 5-HT protein level in blood (;4 ng/ ml), which is doubled by cigarette smoking for 6 wk in rats (53).…”
Section: Discussionsupporting
confidence: 87%
“…PCFs are critical for the generation of central origin apnea (13,14), and, upon activation, 5-HT receptor 3 (5-HT 3 R) in PCFs is capable of inducing an apneic response (15)(16)(17). Although the elevated serum 5-HT levels have been observed in victims of SIDS (18), whether PNE affects the 5-HT level in bronchoalveolar lavage fluid (BALF) and augments the apnea mediated by 5-HT 3 R in PCFs and the relevant mechanism underlying this augmentation remains unknown.…”
mentioning
confidence: 99%
“…Children that die from SIDS breathe normally under normoxic conditions, but fail to gasp during hypoxia (Poets et al 1999;Garcia et al 2013). Various studies also demonstrated dysregulation of 5-HT in SIDS (Broadbelt et al 2012;Massey et al 2013;Rognum et al 2014;Haynes et al 2016Haynes et al , 2017Bright et al 2017). Thus, infants with disturbed 5-HT mechanisms might be protected under normal oxygenated conditions, but become vulnerable to genetic mutations that affect serotonergic neurons when the network transitions into a hypoxic state (Tryba et al 2006;Garcia et al 2013).…”
Section: The Effect Of Hypoxia On the Prebötc In Medullary Slice Rementioning
confidence: 96%
“…Although the above morphometric and neurochemical changes further support a pathogenetic role for central respiratory chemoreceptors, they are still difficult to apply for diagnosis in the forensic context, due to the need for specific methodological experience and proper controls for comparison. Of particular interest is a recent paper which reported higher serum serotonin levels in SIDS victims than in controls, with a subset of 31% SIDS cases with serotonin levels higher than 2 standard deviations above the mean of controls, supporting peripheral anomalies in serotonin metabolism and proposing a simple marker (Haynes et al 2017).…”
Section: Central Respiratory Chemoreceptorsmentioning
confidence: 97%
“…Of particular interest is a recent paper which reported higher serum serotonin levels in SIDS victims than in controls, with a subset of 31% SIDS cases with serotonin levels higher than 2 standard deviations above the mean of controls, supporting peripheral anomalies in serotonin metabolism and proposing a simple marker (Haynes et al . ).…”
Section: Introductionmentioning
confidence: 97%